Room-temperature large magnetocaloric effect and critical behavior in La0.6Dy0.1Sr0.3MnO3. Issue 7 (15th May 2016) - Xu, Lisha; Chen, Lili; Fan, Jiyu; Bärner, Klaus; Zhang, Lei; Zhu, Yan; Pi, Li; Zhang, Yuheng; Shi, Daning
Abstract: The effect of dysprosium incorporation in La0.7 Sr0.3 MnO3 perovskite manganite on its magnetic properties, magnetocaloric effect and critical behavior was investigated. The temperature dependent magnetization data exhibit a sharp paramagnetic–ferromagnetic transition at T C =307 K, which nature has been identified to be a second-order transition by the scaling laws for magnetocaloric effect. The maximum magnetic entropy change and the relative cooling power are found to be, respectively, 8.314 J/kg K and 187 J/kg for a 5 T magnetic field change without a hysteresis loss, making this material a promising candidate for magnetic refrigeration at room temperature. To study the critical behavior of the paramagnetic–ferromagnetic transition, some related critical exponents ( β, γ, and δ ) have been also calculated. The values of critical exponents indicate that the present phase transition does not belong to the common transition classes but shows some abnormal variation. We suggest that the induced lattice disordering and magnetic disordering due to Dysprosium incorporation are essential reasons for the presence of a large magnetocaloric effect and of an anomalous ferromagnetic phase transition in the present material